2010
DOI: 10.1007/s10529-010-0202-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced plumbagin production from in vitro cultures of Drosera burmanii using elicitation

Abstract: Methyl jasmonate, 50 microM, 0.5 mg yeast extract/l and 100 mg chitosan/l stimulated plumbagin production in Drosera burmanii whole plant cultures after 6 days of elicitation. Yeast extract (0.5 mg/l) was the most efficient enhancing plumbagin production in roots of D. burmanii to 8.8 +/- 0.5 mg/g dry wt that was 3.5-fold higher than control plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 14 publications
1
23
1
Order By: Relevance
“…Some species, mainly Drosera rotundifolia L., D. intermedia Hayne and D. anglica Huds., are commonly used in traditional medicine as the therapy of respiratory tract (Paper et al, 2005;Fukushima et al, 2009). Recently, several bioactive compounds from sundew leaves and roots including flavonoids and quinones have been found (Hook, 2001;Marczak et al, 2005;Putalun et al, 2010). These compounds can be considered as very important metabolites (Milella et al, 2011;Padula et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some species, mainly Drosera rotundifolia L., D. intermedia Hayne and D. anglica Huds., are commonly used in traditional medicine as the therapy of respiratory tract (Paper et al, 2005;Fukushima et al, 2009). Recently, several bioactive compounds from sundew leaves and roots including flavonoids and quinones have been found (Hook, 2001;Marczak et al, 2005;Putalun et al, 2010). These compounds can be considered as very important metabolites (Milella et al, 2011;Padula et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a part of the pathogen cellular wall induces a defensive response and, as a result, the naphthoquinone synthesis occurs (Juniper et al 1989). Putalun et al (2010) studied the influence of methyl jasmonate, yeast extract and chitosan. In their study, the yeast extract was found to enhance the production of plumbagin in the roots of D. burmanii by 3.5-fold when compared to the control plants.…”
Section: Elicitation Of Secondary Metabolitesmentioning
confidence: 99%
“…Moreover, high regeneration potential in in vitro conditions has been shown for several members of Droseraceae (Bobák et al 1989(Bobák et al , 1995Š amaj et al 1999;Kawiak et al 2003;Jayaram and Prasad 2008;Grevenstuk et al 2010;Rejthar et al 2014). Since protocols are available for production of valuable metabolites from in vitro cultures, sundew is attractive and promising for biotechnology (Putalun et al 2010). Previously, Król-icka et al (2010) have succeeded in increasing naphtoquinone production in Agrobacterium rhizogenes induced teratomas of in vitro grown Drosera capensis.…”
Section: Introductionmentioning
confidence: 99%